Fritillaria behcetiana (Liliaceae), a new species from eastern Anatolia (Türkiye) - Yapar, Yakup; Tekşen, Mehtap (Phytotaxa, 2025)
Fritillaria behcetiana sp. nov. is described as a new species from Bingöl Province in eastern Anatolia, Türkiye. It is closely related to F. shehbazii, F. chlororhabdota and F. pinardii, but differs from them in several morphological features, including leaf lenght and colour, perianth segment size and colour, anther colour and length, filament length, style lenght and branching. The new species is described in detail, including distribution, ecology, conservation status and photographs with comparisons to F. shehbazii, F. chlororhabdota and F. pinardii.